Effect of Xanthophyll Rich Marigold Petal Meal in the Ration ofCommercial Layers on Egg Composition and Quality Characteristics - Navya, V.G.; Naik, B.Hemla; Thirumalesh, T.; Umesh, B. U.; Rathod, Jyothi M; Bhushan, M. Bharat (Indian Journal of Animal Nutrition, 2025)
The study was conducted to determine the effect of xanthophyll rich marigold petal meal (Tagetuserecta L.) on egg composition and quality characteristics. One twenty Hyline commercial layers (24 weeks old) were divided into five groups of four replication each (six birds in each replication) in CRD. The marigold petal meal (MPM) was incorporated ( % ) in the diet of commercial layers at 0 (T1), 3 (T2), 4 (T3), 5 (T4) and 6 (T5) levels.The CP content of experimental diets ranged from 16.53 to 18.82 per cent and MPM contained 12.49 % CP and 11.43% EE and xanthophylls 2400 mg/kg of petal meal. Due to the inclusion of MPM, egg weight was not affected between the groups. There was no significant effect on egg shell thickness fed with different levels of MPM. Even though there was a significant difference in calcium intake between the treatments, Haugh units, yolk index and albumen index were not affected between the treatment groups. Xanthophyll content of egg yolk, yolk colour and crude protein content were higher as the level of MPM increased in the diet. The inclusion of MPM in the commercial layer diet up to 6 per cent level maintained egg quality parameters as that of control group which indicated that MPM can be safely incorporated beyond 6 percent level in the diet of commercial layers as a source of carotene and protein to improve the egg quality parameters.